The Measurement Of Corporate IT Security Against The Internal Perspective - Andry, Johanes Fernandes; Kurniawan, Febryanto (Technomedia Journal, 2018)
Technology is growing the impact of this technological advances, the Information Technology world at the company is competing to perform a good performance for the company. The level of security in the system in the company becomes important to note because the company has thousands of useful data for the company. The relationship between IT and business processes is closely related to each other and need each other. So in this study pharmaceutical companies located in Jakarta will make measurements of their IT security level and performance of the company's performance. Results maturity level obtained on the DS5 is 1.4, DS7 is 1, DS10 is 1.7, DS11 is 2, and DS13 is 1.8. TI can be concluded that DS5 and DS7 are still initial / ad-Hoc while DS10, DS11, & DS13 are still repeatable but intuTIive. Expected level is Level 3 for the company. IT can be concluded that IT governance in this company in terms of security has effectiveness but not yet maximally in the purpose of its business process, hence this research done to become evaluation company to improve their IT governance.